2008
DOI: 10.1038/eye.2008.265
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy with verteporfin for polypoidal choroidal vasculopathy

Abstract: Background To describe the efficacy of photodynamic therapy (PDT) with verteporfin for the treatment of polypoidal choroidal vasculopathy (PCV). Methods This is a retrospective interventional case series of 41 eyes of 40 patients with angiographic evidence of PCV, which had PDT with verteporfin. Pre-treatment best-corrected visual acuity (BCVA) was measured and patients were followed up for at least 12 months with BCVA recorded at each visit. Results The mean follow-up time was 23.7 months. Seven of 10 eyes (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Numerous case series reported favourable anatomical and VA outcomes for PCV patients treated with verteporfin PDT [9][10][11][12][13][14][15][16][17][18]. Total polyp regression following verteporfin PDT has been reported for up to 21 of 22 eyes (95%) at the 12-month follow-up of individual case series [11], and many patients had stable or improved VA (Table 1), comparing favourably with the natural history of PCV.…”
Section: Verteporfin Pdt In Pcvmentioning
confidence: 71%
“…Numerous case series reported favourable anatomical and VA outcomes for PCV patients treated with verteporfin PDT [9][10][11][12][13][14][15][16][17][18]. Total polyp regression following verteporfin PDT has been reported for up to 21 of 22 eyes (95%) at the 12-month follow-up of individual case series [11], and many patients had stable or improved VA (Table 1), comparing favourably with the natural history of PCV.…”
Section: Verteporfin Pdt In Pcvmentioning
confidence: 71%
“…56,72,109 Lee et al 72 reported 24 of 41 (58.5%) eyes with stable or improved vision (mean follow-up 24 months) and hypothesized that this relatively low rate of success could be attributed to the inclusion of patients with prior laser therapy. Leal et al concluded that, although there was a trend toward progressive loss of BCVA in their prospective study, this was not statistically significant: at 3 years, 74.1% of eyes still had no significant vision loss.…”
Section: Direct Thermal Laser Photocoagulation Still Hasmentioning
confidence: 99%
“…Previous studies reported that visual outcomes after PDT for PCV were unaffected by the presence of a PED 20 but worse in eyes associated with type 2 choroidal neovascularization (CNV). 21 Because most studies on the treatment of PDT for PCV had a relatively small number of eyes, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] we conducted a prospective study of 220 eyes with PCV followed for 1 year after the primary PDT treatment to confirm the factors predictive of VA outcomes 1 year after the primary application of PDT for PCV.…”
mentioning
confidence: 99%